Adaptasi Lintas Budaya Mahasiswa Indonesia di Lingkungan Perguruan Tinggi Taiwan - Rania Alvita Rahma Badri; Kismiyati El Karimah; Yuliani Dewi Risanti Sunarya (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Studying abroad requires students to adapt to new educational systems and cultures. This study explores the cross-cultural adaptation process of Indonesian students in the 2023 Indonesian International Student Mobility Awards (IISMA) Vokasi program in Taiwan. Using a qualitative case study approach, semi-structured interviews and documentation were conducted to examine the multifaceted challenges during a semester-long stay. Findings reveal significant adaptation challenges, including language barriers, non-verbal communication issues, and different educational systems. Students experienced initial stress due to unfamiliar environments, followed by gradual adaptation through proactive engagement and support systems. The study highlights three stages of adaptation: stress, adaptation, and growth, based on Kim's Integrative Communication Theory of Cross-Cultural Adaptation. These stages are supported by personal and social communication, environmental factors, individual ethnic proximity, and adaptive character. Further studies could explore how subcultures from the awardees' home regions influence their adaptation process in different areas of Taiwan, each with its unique Taiwanese subcultural characteristics. Additionally, comparative studies on each awardee by examining the subcultures of their home regions can provide a broader understanding of specific cultural aspects in the cross-cultural adaptation process and improve the development of more effective cultural exchange programs.